Do Do a Macroeconomics Affect on Foreign Direct Investment in Indonesian Firms? - Rollis Ayu Ditasari; Sendy Dwi Haryanto; Rihan Mustafa Zahri (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
Foreign direct investment (FDI) is the first step in development activities and economic growth. This study aims to determine the influence of macroeconomic variables (Inflation, BI Rate, rupiah exchange rate, Gross Domestic Product (GDP), and Foreign Exchange Reserves on Foreign Direct Investment in Indonesia. This research uses quantitative methods of secondary data from the financial statements of companies listed on the Indonesia Stock Exchange in 2016-2022. The results of this study show that only foreign exchange reserves affect Foreign Direct Investment. In contrast, Inflation, BI Rate, Exchange Rate, and GDP do not affect Foreign Direct Investment in Indonesia. Then The results of this study also show that, simultaneously, Inflation, the BI Rate, Exchange Rate, GDP, and Foreign Exchange Reserves significantly affect Foreign Direct Investment.